Unbiased Characterization of Peptide-HLA Class II Interactions Based on Large-Scale Peptide Microarrays; Assessment of the Impact on HLA Class II Ligand and Epitope Prediction - Wendorff, Mareike; Garcia Alvarez, Heli M.; Østerbye, Thomas; ElAbd, Hesham; Rosati, Elisa; Degenhardt, Frauke; Buus, Søren; Franke, Andre; Nielsen, Morten (Frontiers in Immunology, 2020)
Human Leukocyte Antigen class II (HLA-II) molecules present peptides and play an essential role in adaptive immune responses. Characterizing the binding specificity of single HLA-II molecules has profound impacts for understanding cellular immunity, identifying the cause of autoimmune diseases, for immunotherapeutics and vaccine development. Here, novel high-density peptide microarray technology and machine learning techniques were used to address this task at a level of high-throughput that goes well beyond the limitations of alternative technologies. Microarrays with over 200,000 defined peptides were assayed with five exemplary HLA-II molecules. Machine learning was applied to mine the signals. The comparison of identified binding motifs, and power for predicting eluted ligands and CD4+ epitope datasets to that obtained using NetMHCIIpan-3.2, confirmed a high quality of the chip readout. These results suggest that the proposed microarray technology offers a novel and unique platform for large-scale unbiased interrogation of peptide binding preferences of HLA-II molecules.